2013
DOI: 10.1186/1756-3305-6-314
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Kato-Katz method and formalin-ether concentration technique for the diagnosis of Clonorchis sinensis, and implication for assessing drug efficacy

Abstract: BackgroundClonorchiasis is a chronic neglected disease caused by a liver fluke, Clonorchis sinensis. Chemotherapy is the mainstay of control and treatment efficacy is usually determined by microscopic examination of fecal samples. We assessed the diagnostic accuracy of the Kato-Katz method and the formalin-ether concentration technique (FECT) for C. sinensis diagnosis, and studied the effect of diagnostic approach on drug efficacy evaluation.MethodsOverall, 74 individuals aged ≥18 years with a parasitological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 35 publications
(36 reference statements)
1
21
0
2
Order By: Relevance
“…Recently we found that C. sinensis were able to mature and release eggs in BALB/c mice [ 9 ]. In this study, fecal examination was also performed by modified Kato-Katz egg counting technique [ 9 , 29 ] to further confirm the egg production capacities of the worms. However, no eggs were found in the faeces from both TLR2 wild-type and mutant mice after the infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently we found that C. sinensis were able to mature and release eggs in BALB/c mice [ 9 ]. In this study, fecal examination was also performed by modified Kato-Katz egg counting technique [ 9 , 29 ] to further confirm the egg production capacities of the worms. However, no eggs were found in the faeces from both TLR2 wild-type and mutant mice after the infection.…”
Section: Discussionmentioning
confidence: 99%
“…Stool samples were collected from each infection group every other day and were mixed together every 20 days. Eggs were counted by the Kato-Katz egg counting technique [ 29 ]. For perfect blending, 1 ml of pure water was added into 1 g of stool of each sample.…”
Section: Methodsmentioning
confidence: 99%
“…The stool samples were thoroughly mixed after complete humidification. Triplicate Kato-Katz thick smears using standard 41.7 mg templates [ 24 ] were prepared from each stool sample. The number of C. sinensis eggs was counted and presented as the geometric mean of eggs per 1 g of stool (GM EPG).…”
mentioning
confidence: 99%
“…Contradictory results have been reported in the literature on the effectiveness of Kato-Katz and Formolether techniques in the detection of gastrointestinal parasites in faeces. Some authors have noted that the Kato-Katz technique was better and significantly more sensitive than the other method (18)(19) while others have reported that the Formol-ether technique had a better sensitivity than the Kato-Katz method (20)(21). According to Knight et al, (22), the concentration of eggs in the faeces enabled the detection of more patients infected with S. mansoni when the Formol-ether technique was used.…”
Section: Discussionmentioning
confidence: 99%